Ikat Weaving Dayak Desa: The Meaning of Local Wisdom Values in Ensaid Panjang Village - Ananda, Fransiska Yusi; Chalimi, Ika Rahmatika; Mirzachaerulsyah, Edwin (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
The Dayak tribe, as a tribe with a large number of sub-ethnic groups and a diverse culture, has one community group that still maintains a tradition passed down through generations of weaving activities, namely the Village Dayak Tribe who live in South Rentap Hamlet. The aim of this research is to determine the value of local wisdom contained in Village Dayak ikat woven fabric motifs. This research uses qualitative methods with a descriptive-ethnographic approach. Based on the research results, it shows that the process of designing Village Dayak ikat woven cloth motifs is called the ngebat process. Ngebat is a way of designing ikat woven fabric motifs by tying certain parts of several pieces together using neat rope or plastic. The local wisdom values contained in every Dayak Desa ikat woven cloth motif have very strong values and philosophies in the lives of the people in Ensaid Panjang Village. Through the motifs in ikat fabrics, people are taught how we as humans should position ourselves in social life and how we can meet various daily needs. Forms of preserving local wisdom in Dayak Desa ikat woven fabric include promoting it on social media, exhibiting it in museums, having its motifs recorded, selling it and using it at official or unofficial events.